TMIC-02. JUNCTIONAL ADHESION MOLECULE-A (JAM-A) DEFICIENCY DRIVES SEX-SPECIFIC DIFFERENCES IN GLIOBLASTOMA PROGRESSION VIA DIFFERENTIAL MICROGLIA RESPONSES IN THE TUMOR MICROENVIRONMENT. (11th November 2019) - Turaga, Soumya; Silver, Daniel; Paouri, Evi; Bayik, Defne; Peng, Sen; Connor, James; Barnholtz-Sloan, Jill; Rubin, Joshua; Berens, Michael; Davalos, Dimitrios; Lathia, Justin
Abstract: Despite the male preponderance for developing glioblastoma (GBM) and better survival outcomes in females, current treatment paradigms do not account for biological sex as a biological or clinical variable. Sex-specific molecular alterations that drive tumor cell growth and therapy response have been documented, however, sex-specific extrinsic differences in the tumor microenvironment have yet to be identified. Based on well-established sex-specific gene signatures and functional differences in microglia, we interrogated influences of male and female microglia in driving GBM growth. Specifically, manipulation of JAM-A expression, a tight junction protein on microglia, was exploited as a paradigm for determining effects on in vivo syngeneic GBM mouse models. Male and female JAM-A KO mice that received orthotopic injection of syngeneic GBM cells presented differential overall survival distinct from their wildtype counterparts. Wild-type male mice phenocopied human males, presenting shorter overall survival than females, this trend was reversed in JAM-A KO mice. Compared to the other genotypes, female JAM-A KO mice presented the greatest number of phagocytic, tumor-promoting, activated microglia. RNA-sequencing of tumors from JAM-A KO and WT mice revealed that female JAM-A KO mice had increased expression of Ifi202b (interferon activated gene 202b), a member of the Activity-regulated Inhibitor of Death (AID) gene family that contributes to mitochondrial resistance to cellular stress. Ifi202b has a role in sex-specific inflammatory diseases, which is consistent with our observation. Female KO microglia had enhanced Ifi202b expression, along with the secretion of Ifi202b associated cytokines, including interleukin-6. Treatment of wild-type female microglia with a JAM-A function blocking antibody demonstrated an increase in Ifi202b levels, confirming direct regulation of Ifi202b expression by neutralizing JAM-A. While cell intrinsic, sex-specific differences have been reported in GBM, our findings demonstrate that differences in the GBM tumor microenvironment also drive sexually dimorphic tumor growth.